ASUHAN KEPERAWATAN PADA KLIEN POST OP FRAKTUR CRURIS DENGAN MASALAH KEPERAWATAN NYERI AKUT (STUDI LITERATUR): ASUHAN KEPERAWATAN PADA KLIEN POST OP FRAKTUR CRURIS DENGAN MASALAH KEPERAWATAN NYERI AKUT (STUDI LITERATUR) - zuliani, zuliani; Kurniawan, Mohammad Alfin; Nisa, Nurul Khoirun (WELL BEING, 2021)
Post op fracture of the cruris is a break in the tibia and fibula. Clinically, it can be an open fracture if it is accompanied by damage to the soft tissues muscle, skin, nerve tissue, and blood vessels, allowing the connection between the broken bone fragments with the outside air and the closed fracture. The impact that trauma can have on a fracture is limited to activity, may have the change in the damaged part of the body an the anxiety that may result from pain and pain. This research method used a literature study with a case study of nursing care in post op cruris fracture patients with acute pain problems in the Asoka Pavilion of Jombang Hospital which was carried out in the 2017-2019 period. The results of the literature study show that the priority problem for post op client cruris fracture is acute pain. The literature study of 4 clients showed that there were similar factors causing pain in the post op wound fracture of the cruris which resulted in decreased muscle strength, swelling, dan CRT> 2 seconds. Surgery will produce damaged cells with the consequence that it will release autanoid chemicals that can cause pain. Efforts to cope with injuries from post op cruris fracture by performing techniques in the greeting relaxation activities and listening to music and pain medication. In order to recover wounds from post op fracture, the cruris fracture should be treated routinely and increase their nutritional intake